Aktivitas Fisik Lansia untuk Mengontrol Hemodinamik melalui Kombinasi Senam Tera dan Senam Pernapasan (SETAPA) pada Lansia dengan Hipertensi - Isnaeni, Isnaeni; Ikmawati, Isna; Asiandi, Asiandi; Riyaningrum, Wahyu (Jurnal Riset Kesehatan Masyarakat, 2023)
Background: The prevalence of hypertension increases with age. Hypertension in the elderly is caused by a disturbance in the cardiovascular system. Hypertension is a degenerative disease that can cause death. Reducing hypertension can be done with non-pharmacological handlers. One of the non-pharmacological treatments is by doing physical activity, one of which is combining therapeutic exercises and breathing exercises. Objective: To determine the effect of a combination of tera and breathing exercises (SETAPA) on hemodynamics in the elderly with hypertension. Methods: The study used a pre-experimental design, with a one-group pre-test and post-test approach. Sampling used purposive sampling, inclusion criteria aged 60-75 years, with a total sample of 56 respondents using a categorical descriptive sample formula. Results: The results showed that the average age of most respondents was 60-64 years old. Most of the respondents were female, namely 54 people (96.4%), and male, namely 2 people (3.6%). The average systolic blood pressure before the intervention was 148.21 mmHg and after the intervention was 133.66 mmHg. And the average diastolic blood pressure before the intervention was 90.36 mmHg and after the intervention was 82.86 mmHg. The results of the Wilcoxon test analysis showed that there was a difference in the average blood pressure before and after the intervention with a systolic blood pressure p = 0.001, a diastolic pressure p = 0.001 with a large effect size (Large effect) on systolic blood pressure of -0.82 and diastolic blood pressure of, -0.57. Conclusion: There is a combination effect of tera exercise and breathing exercise (SETAPA) on reducing blood pressure in the elderly with hypertension.